Contribution of Vision, Touch, and Hearing to the Use of Sham Devices in Acupuncture-Related Studies - Chee-Wee Tan; Derek Santos (Medical Association of Pharmacopuncture Institute, 2020)
This study investigates whether visual deprivation influences participants' accuracy in differentiating between real and sham acupuncture needles. It also evaluates the relative contributions of tactile, visual, and auditory cues that participants use in their decision-making processes. In addition, a simple sensory decision-making model for research using acupuncture sham devices as comparative controls is proposed. Forty healthy individuals underwent two conditions (blindfolded and sighted) in random sequence. Four sham and four real needles were randomly applied to the participants' lower limb acupoints (ST32 to ST39). Participants responded which needle type was applied. Participants then verbally answered a questionnaire on which sensory cues influenced their decision-making. The proportion of correct judgments, P(C), was calculated to indicate the participants' accuracy in distinguishing between the needle types. Visual deprivation did not significantly influence the participants' discrimination accuracy. Tactile cues were the dominant sensory modality used in decision-making, followed by visual and auditory cues. Sharp and blunt sensations were associated with the real and sham needles, respectively, for both conditions. This study confirmed that tactile cues were the main sensory modalities used in participant decision-making during acupuncture administration. Also, short-term blindfolding of participants during procedures will unlikely influence blinding effectiveness. Clinical trial registration number: Not applicable. This study does not fall under the definition of a clinical trial under the ICMJE guidelines. Keywords: acupuncture points, cues, decision-making, humans, sensation